2010
DOI: 10.1680/udap.2010.163.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Gated communities: definitions, causes and consequences

Abstract: Gated communities became an 'object of study' in the 1990s as social scientists observed their growth in several cities; they are now a feature of the urban landscape in most cities around the world. The expansion of gated communities has led to prolific research, examining different aspects of this type of residential development and providing evidence from case studies worldwide. This paper reviews how gated communities are conceptualised according to the literature and identifies the main factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 20 publications
1
39
0
13
Order By: Relevance
“…Negative term of gated community Roitman (2010) describes that the existence of individual desires, interests, perspectives and opportunities triggers subjectivity from the expansion of the gated community. The causes of subjectivity include: finding social homogeneity, the desire to have a feeling of togetherness in a community, having a high fear of experiencing crime, seeking a better lifestyle, and hoping to have a higher social status and be able to show social differences in particular social groups.…”
Section: Types Of Gated Communitymentioning
confidence: 99%
See 2 more Smart Citations
“…Negative term of gated community Roitman (2010) describes that the existence of individual desires, interests, perspectives and opportunities triggers subjectivity from the expansion of the gated community. The causes of subjectivity include: finding social homogeneity, the desire to have a feeling of togetherness in a community, having a high fear of experiencing crime, seeking a better lifestyle, and hoping to have a higher social status and be able to show social differences in particular social groups.…”
Section: Types Of Gated Communitymentioning
confidence: 99%
“…Edgü & Cimşit (2011) found that living in a gated community usually resides in smaller and more limited residential units, residents provide a number of facilities for social adaptation, and increasing social relations, so that have an impact on satisfaction for the neighborhood in that community. Roitman (2010) explains the existence of subjective causes including an increase in fear of crime, a matter of improving lifestyle, a sense of belongingness in a community, social homogenies, social status aspirations, and social differentiation in certain social groups. Furthermore, Edgü & Cimit (2011) added that security would be maintained if living in this environment because of the limited housing units, facilitated by the social adaptation of its inhabitants, and the consequence was occupant satisfaction.…”
Section: Types Of Gated Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…The social composition of suburbia has changed. However, this is one of the main differences with the Anglo-American 9 For a detailed analysis of the reasons behind choosing to live in gated communities in Argentina, see Roitman (2010).…”
Section: Suburban Growth and Gated Communities In Argentinamentioning
confidence: 99%
“…Edward J. Blakely (1999) (Ellin, 2001;Webster, 2001;Stoyanov in Frantz, 2006;Roitman, 2010, ter Ülkü in Erten, 2013, nedvomno pa se bodo s tem dvignile tudi cene nepremičnin v OS (Blakely, 1999, ter Bible in Hsieh, 2001). Opomba: OSH = ograjena skupnost Hamravat (n = 33), OSG = ograjena skupnost Gekušagi (n = 27); * p < 0,05.…”
Section: Preference Povezane Z Os In Razlogi Zanjeunclassified